Navigating the new normal: how social support affects mental health among international postgraduate students at the faculty of health sciences, UKM - Ahmad Rohi Ghazali,; Mahmoud M. Dboba,; Alshangeeti Tahani Mostafa M,; Israa Abdul Sattar Ali Al Sammarraie,; Wang Li,; Taufik Hidayat,; Wong Yee Yan,; Raveena Vaidheswary Muralitharan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has completely changed how we go about our daily lives. Such drastic changes may lead to psychological distress such as depression, anxiety and stress. This is especially challenging for international students, particularly the postgraduate students as they face additional difficulties in adapting to a new teaching and learning environment. Hence, as we transition to a new normal era, it is pertinent that we investigate how existing forms of social support play a role in helping international postgraduates cope with their depression, anxiety and stress. The research aimed to determine the relationship between social support, depression, anxiety and stress among international postgraduate students at the Faculty of Health Sciences (FSK), Universiti Kebangsaan Malaysia (UKM). The findings revealed that 27.8% of students exceeded the normal range for depression, 50% exceeded the normal range for anxiety, and 11.1% exceeded the normal range for stress. Next, there was no relationship between social support with depression, anxiety and stress. However, there were significantly strong positive relationships between depression, anxiety and stress. Then, there was no significant difference in depression, anxiety and stress between male and female international postgraduate students. Lastly, when social support was suggested (eight types) to be given, the students did not prefer a particular type of social support over others, but each type of social support suggested was still needed by the students.